ON A CONJECTURE OF P. NYLEN AND L. RODMAN - Rakočević, Vladimir (Matematichki Bilten, 1993)
In this note we prove that conjecture of P. Nylen and L. Rodman [2, Integral Equations and Operator Theory, Vol. 13(1990), 728-749] is true.